A Framework for Developing a Model Structure of Budget Impact Analysis for New Health Care Interventions in Jordan - Massad, Eman Mohammad; Bakir, Amir (International Journal of Economics and Financial Issues, 2021)
This paper assesses the impact of substituting clopidogrel with ticagelor to treat patients after an acute attack of Ischemic Heart Disease from the perspective of Jordanian MOH in its tenders, using Budget Impact Analysis (BIA). A multiple regression analysis used to estimate the elasticities associated of implementing the two treatments, and then Matlab used to compare the old and new treatments. The study recommends the gradually substitution of the new treatment using ticagelor because it achieves total cost savings of approximately 200,000 Jordanian dinars, and that the flexibility of the new treatment costs is less than in the case of the old treatment, which means that the increase in numbers of patients will lead to a lower increase in the total costs when using the new treatment. Keywords: Budget Impact Analysis, acute coronary syndrome, ticagrelor. JEL Classifications: I11, I15, I19 DOI: https://doi.org/10.32479/ijefi.10573